Implementasi Sistem Elektronik dalam Meningkatkan Kepatuhan Wajib Pajak - Dewi, Ni Nyoman Sri Rahayu Trisna (E-Jurnal Akuntansi; Vol 34 No 1 (2024)DO - 10.24843/EJA.2024.v34.i01.p18, 2024)
This research aims to determine the effect of implementing e-billing and e-filing on taxpayer compliance. Research data was collected using a questionnaire. This research uses individual taxpayers at KPP Pratama West Denpasar as respondents with a total of 100 respondents. The data analysis method used in this research is multiple linear regression analysis using the SPSS program. The research results show that the implementation of e-billing and e-filing can increase taxpayer compliance at KPP Pratama West Denpasar. Keywords: E-Billing; E-Filing; Taxpayer Compliance